Marayniyoq, un establecimiento wari en el valle de Ayacucho, Perú - Valdez, Lidio M.; Valdez, J. Ernesto; Bettcher, Katrina J.; Vivanco, Cirilo (My University, 2000)
In this paper we discuss the initial results of archaeological excavation carried out at Marayniyoq, a specialized Wari facility in the Ayacucho Valley, Peru. The discovery of a series of flat worked stones used for grinding, along with rocker grinders strongly suggests that the role of Marayniyoq was focused on grain processing, probably grinding corn. Because the grinding stones are immense cut blocks it is also apparent that enormous human energy was invested in the preparation, transportation and final setup of the facility. At the same time, the presence of large ceramic vessels and other evidence suggests that the function of Marayniyoq was the grinding of malted corn (qora) for corn-beer production.
Marayniyoq, a Wari facility in the valley of Ayacucho, Peru
Keywords: Middle Horizon; grinding stones; Ayacucho; Peru